Revendication des droits civiques et préparation au « jour J » : mobilisation et stratégies des féministes radicales allemandes pour obtenir le droit de vote (années 1890-1918) - Anne-Laure Briatte (Genre & Histoire)
This article traces the struggles of German “radical” feminists in enabling and preparing for women’s access to the right to vote and to stand for election. Drawing on articles in the fortnightly journal Die Frauenbewegung (The Women’s Movement), the official press organ of the “radical” bourgeois women’s movement, and on pamphlets and memoirs published by “radical” feminists, it shows that, starting from a somewhat idealized conception of Parliament and relying heavily on this to defend women’s interests, “radical” feminists gradually domesticated politics, through their symbolic entry into the political arena and through the subjects they managed to place on the agenda of parliamentary debates. Finally, the article presents elements of the feminists' debate on how best to promote and prepare for women’s entry into politics, either in separate action or by working alongside men.